A pilot study using magnetic resonance imaging to determine the pattern of muscle group recruitment by rowers with different levels of experience - Green, R. A.; Wilson, D. J. (Skeletal Radiology, 2000)
OBJECTIVE: To determine whether it was possible using magnetic resonance imaging (MRI) to define the pattern of muscle recruitment in a specific sport (rowing) and to see whether there were differences in this pattern between athletes of different experience. DESIGN AND METHOD: It has been shown that during vigorous exercise the water content of muscle increases transiently. This can be observed using MRI, where the prolonged T2 relaxation time of muscle can be demonstrated. In this study we have exploited the increase in signal seen in exercised muscle on short TI inversion recovery (STIR) sequences, to show how rowers of different experience use different muscle groups. RESULTS: We have shown that trained athletes recruit selected muscle groups to carry out a given task, which they carry out more efficiently than untrained or less experienced athletes. CONCLUSION: We have provided the basis of potential research to refine training methods, in order to develop specific muscle groups in athletes, in the hope of achieving a higher level of performance at an earlier stage in their training. We have also defined a technique that may be of clinical value in cases of muscle dysfunction.